'A town new and modern in conception': non-racial dreams and racial realities in the making of Gaborone, Botswana. (2nd January 2019) - Marr, Stephen
ABSTRACT: Botswana has long been praised for its financial and political achievements. High economic growth rates and uninterrupted democratic governance since independence in 1966 have led to Botswana's labeling as the 'African Miracle'. Long before Botswana's emergence as a darling of Western development agencies however, Tswana elites and colonial officials also saw Botswana as exceptional: surrounded by states divided along racial lines, these individuals sought to construct a nation organized around principles of racial and tribal unity. Aspirations of non-racialism were to be exemplified in Botswana's newly constructed capital city, Gaborone. At the same time, underlying the planning vision for Gaborone was a competing set of narratives, practices and aspirations that undercut these lofty ideals and resulted in the creation of a city highly stratified by racial segregation. This essay identifies three complementary urban planning rationales that produced urban exclusion in Gaborone: the desire to build Gaborone as an administrative capital, borrowing from both colonial and indigenous Tswana traditions that privileged spatial divisions related to status and race, and the goal to build a 'modern' urban center to lead Botswana into the future. These tensions divided the city in ways both familiar and unexpected and set the parameters determining who counts as a legitimate resident of the city. The paper, therefore, seeks to explore how a city founded on an ideal of racial unity instead became a site of stark division(s).